PENERAPAN STEM BERBANTUAN MEDIA PEMBELAJARAN GEOGEBRA TERHADAP MOTIVASI BELAJAR SISWA - Devi Ana (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2023)
This study aims to determine the effect of mathematics learning assisted by geogebra learning media on the learning motivation of class X senior high school students in geometric materials. This research is a quasi-experimental research with the dependent variable of student learning motivation and the independent variable is STEM assisted by geogebra learning media. The research design is a nonequivalent control group design. The research subjects were 68 students. The data collection instruments used were mathematics learning achievement tests and learning motivation questionnaires. The data were analyzed by covariance analysis with pre-test scores as covariates at a significance level of 5% (d = 0.05. The results of this study were; the application of STEM assisted by Geogebra learning media had a positive effect on student learning motivation. The results of the covariance analysis showed that the value was sig.0.001 < 0.05.